APPLICATION ANALYSIS OF COOPERATIVE METHODS TO INCREASE LEARNING MOTIVATION OF STUDENTS IN CLASS 3 SDN CANGGU 1 - Betty Oktavia Rahmayanti; Agung Setyawan (Citra Dharma Cindekia, 2022)
Learning motivation is one of the important components that must be owned by every student in the learning process so that learning objectives can be achieved as expected. One of the learning methods that can be applied in order to increase student learning motivation is the cooperative method. The purpose of this study was to analyze the increase in learning motivation of grade 3 students through the application of cooperative learning methods. The population used in this study were all grade 3 students of SD Negeri Canggu 1 for the academic year 2021/2022. Meanwhile, the sample in this study was some of the 3rd grade students of SDN Canggu 1 in the 2021/2022 academic year. Data collection techniques used are interviews, observation, documentation, and literature study. The data analysis technique used in this research is reduction, data presentation, and conclusion drawing. The results of the analysis show that there is a significant increase in students' learning motivation when teaching and learning activities use cooperative learning methods. This research can be used as input for educators to choose innovative learning methods to increase students' learning motivation.